Soldiers, pioneers, & Indian people : positive interaction between cultures in southeastern Washington - Schulz, Laura (Laura Suzanne) (Fort Walla Walla Museum, 2007)
Accompanies the Lloyd family Indian artifact collection, which consists of more than 250 artifacts, photographs, and documents of regional Indian significance including Cayuse, Nez Perce, Palouse, Umatilla, Walla Walla, Wanapum, and Yakama people.